Analisis Gaya Kepemimpinan Pemerintah dalam Meningkatkan Efektivitas Administrasi Publik - Khalida Rea, Kean; Saepudin, Eli Apud; Ester S, Amanda; Anggraeni, Osi; Yuliyani, Yuliyani; Rachmawati, Elza (UNIVERSITAS SERAMBI MEKKAH, 2025)
This article analyzes government leadership styles in improving the effectiveness of public administration in Indonesia. In the context of an increasingly complex government, the leadership style applied by leaders has a significant impact on the performance and responsiveness of public administration. This research uses a qualitative approach with data collection through interviews, observation, and document analysis. The results show that transformational and participatory leadership styles tend to be more effective in encouraging innovation, collaboration, and improving public services. In contrast, authoritarian leadership style is proven to hinder communication and trust between the government and the community. The findings suggest the need for the development of adaptive and inclusive leadership competencies to achieve the goal of better public administration goals. It is hoped that this article will provide insight for policy makers in formulating leadership strategies that can increase the effectiveness of public administration in the future.